Inovação sustentável na indústria do Estado de Mato Grosso: setores de alimentos e madeireiro (1970-2012) - SILVA, Ivana Aparecida Ferrer (Universidade Federal do Pará, 2013)
The economic growth of Mato Grosso in the last four decades is presented as a reflection of public policies implemented in the state, although the direction for the commoditie´s production has generated significant impacts on the environment and in the local society. Moreover, sustainable innovation in industries might become a factor of diversification and optimization of industrial production matrix of the state. Thus, the objective of this thesis is the ability to detect adherence of Food and Wood industries of Mato Grosso over the paradigm of sustainable innovation. The exploratory study was operationalized through a field study in which 1149 industries formed the universe, a random with 92 responses of entrepreneurs, 57 wood´s and 35 food´s supply. The data collected from January to July 2012 were statistically analyzed by SPSS 17. Such analyzes have revealed that sustainable innovation is not yet configured as a reality, lacking basic structural conditions to enable the operation of the system, however there is strong evidence that entrepreneurs are pursuing innovation in processes, seek information, encouraging their employees to innovate and already adopt some practices related to sustainable management. There is a dichotomy in the profile of companies in the state and also in the way they seek to innovate, so that public policies do not meet all evenly. Few companies effectively develop sustainable innovation, largely acquire foreign technology. Besides the quantitative research were technical visits and interviews in eleven public institutions in order to collect qualitative information about the industry and their adherence to sustainable innovation. This study confirmed the hypothesis that public institutions were inefficient in the process of "sustainable regional development", as generated only economic growth. And are responsible for the current production structure that excluded indigenous or autoctone knowledge and territorial characteristics, to established and maintain the path dependence. However there is the possibility of transforming these productive structures since the institutionalities be transformed and education, learning and support structures to micro and small business owners are strengthened through cooperation. Guidelines were suggested.